Kesesuaian Pemanfaatan Ruang Terhadap Pola Ruang Pada Kecamatan Samboja Kabupaten Kutai Kartanegara: Suitability of Space Utilization - Irfan Wahyudi; Umar Mustofa; Dwinsani Pratiwi Astha; Devi Triwidya Sitaresmi (COMPACT: Spatial Development Journal, 2023)
Spatial planning is needed in an area so that regional growth is synergistic with the spatial pattern plan in the future. Spatial planning that is not good will have an impact on other aspects such as the economy, social and culture, so spatial control is needed to avoid complex risks that will occur in various aspects. Samboja Subdistrict has a tendency to develop areas that are in coastal or seaside areas and there are many illegal mines, and will become the central area of ​​agro-industrial and food industry areas in the new National Capital (Nusantara) plan. Based on these problems, a study was conducted to determine the suitability of spatial use against spatial patterns in Kutai Kartanegara District. In achieving the objectives of the problem is carried out using the method in this study, namely using data collection methods in the form of secondary surveys, namely agency surveys with data analysis methods, namely spatial analysis in the form of overlays.